COMMUNITY PERCEPTION AROUND HALFWAY HOUSE ABOUT CARE OF MENTAL DISORDERS - Farah Aulia Nughraini; Ah Yusuf; Ni Ketut Alit Armini (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2021)
Introduction: The high stigma in the community towards mental disorders does not only affect families and mental disorders patients but also on the patterns of care and care, for example, mental disorders patients are isolated so they do not interact with the community with shackles. The purpose of this research is perceptions in the community about how to treat patients with mental disorders.Method: This study used a qualitative research design with a phenomenological approach with ten participants. The technique of selecting participants was purposive sampling with the criteria of men and women aged > 17 years, living around halfway house and who had interacted with mental patients at halfway house. Retrieval of data on ten participants with in-depth interviews and field notes were then analyzed using the Colaizzi method.Results: In this study, 8 themes were identified, namely 5 themes (community understanding of mental disorders, community stigma, community response, community expectations and community experiences with mental patients) for the first specific purpose and 3 themes (treatment, form of care and caregiver factors nurse) for the second special purpose.Conclusion: Community perception is influenced by several factors including the factor of maintaining distance from mental patients, tolerance and support factors, social limitation factors, and factors of prejudice and misunderstanding. Future research can explore in-depth people's perceptions about the treatment of mental disorders patients, more specifically, for example, the care of mental patients in hospitals and at home.